Mr. Emerson's cook - Schachner, Judith Byron (Dutton Children's Books, 1998)
Annie Burns answers an ad requesting an extraordinary cook needed to get Mr. Emerson to eat real food to supplement the nourishment he derives from nature through his imagination.